Triboelectric nanogenerators for marine energy harvesting and sensing applications - Sithara Radhakrishnan; Sherin Joseph; E.J. Jelmy; K.J. Saji; T. Sanathanakrishnan; Honey John (Results in Engineering, 2022)
Triboelectric nanogenerators (TENG) are emerging as a potential technology in the wave energy harvesting domains due to their attractive characteristics like robust structure, ease of material selection, facile fabrication, high sensitivity, and high output. Since TENG enables the harvesting of random, multidirectional, low-frequency mechanical motions, its applicability can be easily extended to harvest the most underutilized renewable energy source - wave energy. This review article discusses the latest developments in marine energy harvesting and self-powered sensors using TENG. The study covers the basic understanding of TENG, its development pathways, working principle, and standard operational modes and focuses on the reported works on wave energy harvesting and self-powered sensing applications. Though various studies have been reported in lieu of wave energy harvesting, the immense possibilities of improvement of structure and materials do exist. More exploration of bionic structures and superhydrophobic materials for liquid-solid interface TENG will be a breakthrough in renewable energy harvesting.